Guidelines for covering online surveys - Abbas Hashim, Muslim (ALBAHITH ALALAMI, 2022)
Media and communication's research are varied in accordance to research approaches' variety which seeks to reach convergent social, psychological, political, economic, and technical point of views. Its main aim is to assimilate all the new variables in the communicative method, especially, social media sites research; concerning their methodology, tools and theories. It is due to their diverse - developed applications and their increased rates of public use becoming irreplaceable in our daily life. It is well reflected by their consequent impact on the the public beside their role in changing its views.This clarifies the notable increase of scientific research that concern them manifesting the dialectical relations and interference between the digital tools and domains of humanities. It, also, concerns their role in broadening the horizons of humanities research shifting from being software’s, only, to tools of textual and visual analysis.Communication studies follow the nature of the method dedicated to convey the communicative message. Hence, the development of the method must be parallel to that one of the studies. In fact, the communicative method adds new dimensions to the communication process revealing the relations and ties that connect communication's process with other processes within the society's cultural structure.